Note on the Numerical Solutions of the General Matrix Convolution Equations by Using the Iterative Methods and Box Convolution Product - Adem Kılıçman; Zeyad Al zhour (Abstract and Applied Analysis)
We define the so-called box convolution product and study their properties in order to present the approximate solutions for the general coupled matrix convolution equations by using iterative methods. Furthermore, we prove that these solutions consistently converge to the exact solutions and independent of the initial value.